Microsoft visual C++/CLI step by step - Templeman, Julian (Delhi PHI Learning, 2014)
Expand your expertise--and teach yourself the fundamentals of the Microsoft Visual C++/CLI language.
Includes index
Keywords: C++/CLI (Computer program language); C++ (Computer program language); Microsoft .NET Framework